Pengaruh Digital Marketing Dan Kepercayaan Pelanggan Terhadap Kepuasan Pelanggan Pada Usaha Jastipyane.Mof Di Maumere - Lengari, Mauresia Pihok Peni; Rangga, Yoseph Darius Purnama; Gula, Valeria Eldyn (Universitas Nusa Nipa Maumere, 2026)
This study aims to determine and analyze the effect of digital marketing and customer trust on customer satisfaction at the Jastipyane.mof courier/jastip service business in Maumere. The background of this research is based on the rapid growth of the personal shopper (jastip) business, which increasingly relies on digital technology for marketing activities, and the critical importance of building customer trust in online transactions. The problems identified at Jastipyane.mof include sub-optimal digital marketing management, slow response to customer inquiries, and a satisfaction performance gap discovered during pre-survey. This study utilizes a quantitative approach with a survey method. The population consists of all 1,990 customers of Jastipyane.mof in Maumere. The sampling technique employed was purposive sampling, resulting in 95 respondents calculated via the Slovin formula. Data analysis techniques include descriptive statistics, validity and reliability testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination administered via SPSS. The results demonstrate that digital marketing has a positive and significant partial effect on customer satisfaction. Customer trust also exerts a positive and significant partial impact on customer satisfaction. Simultaneously, digital marketing and customer trust have a positive and significant combined effect on customer satisfaction at Jastipyane.mof in Maumere.